Evaluating the level of fungal contamination in ready-made feed used in some broiler farms (Journal of Hama University, 2025)
This study aimed to evaluate the level of fungal contamination of both starter (mashed) and finisher feed used on six different farms dedicated to raising poultry (broilers) in Tartous Governorate - Syria, during the period from October 2023 to February 2024; By growing samples of these feeds in the laboratory on Potato Dextrose Agar (PDA) culture, to estimate the level of fungal contamination according to the number of colony forming units in one gram of each sample Colony Forming Unit/Gram (CFU/g), as there is no local information available on the level of fungal contamination in poultry feed. The results showed that the average level of fungal contamination in the starter feed (38.83 X 102 CFU/g) was significantly higher (P < 0.05) than the finisher feed (10.92 X 102 CFU/g). It was also shown through evaluating the quality of the feeds that all samples of the starter feed (100%) violated the European standard (103 CFU/g), while one sample was of the finisher feed (17%) violated the European standard for ready-made poultry feed. This study concluded that evaluating fungal contamination in poultry feed deserves great attention, and that this method is suitable for conducting quality assessment of poultry feed. This study recommends following biosecurity procedures to improve the quality and cleanliness of feed, and conducting periodic evaluation of poultry feed, in addition to accelerating the development of a special local standard for evaluating fungal contamination in poultry feed.
Keywords: Ready-Made Feed, broiler Farms, Fungal Contamination, Evaluation.